AI Music Generator (Journal of Pharmaceutical Negative Results, 2022)
Artificial intelligence is the study and creation of machines that can perform tasks that would ordinarily require human intelligence such as face detection, speech recognition, and decision-making. We will be using deep learning as a source to generate music through a computer using a database of music tunes without any expertise of any trained music artist. The music is generated through sentimental analysis, which helps in mood detection through a sample image of a human self. The music is stored as a piano-roll which is divided in several types of emotions that is generated through the testing process. The use of deep learning is that the machine trains itself through iteration of inputs that is provided in the database which will help in generating music from the input of a face of the user and will make music generation easier. The various models of deep learning are LSTM, CNN, GAN and many more that help in music generation and simultaneously help in enhancing the exposure to sentimental analysis. This project will be using some of these models to demonstrate music generation through sentimental analysis.